Smart living: cafetería virtual para la Institución Universitaria Antonio José Camacho (2020)
The Smart Campus ecosystem macroproject, carried out at UNIAJC, seeks to impact the community in general through the optimization of institutional services. These improvements are framed within projects that, in cases like the one in this article, are supported by undergraduate projects and in others directly by the team of fellows of the Directorate of Information and Communication Technologies of the university. All the solutions generated from Smart Campus are oriented in 6 axes: Smart People, Smart Goverment, Smart Enviroment, Smart Mobility, Smart Economy and Smart Living. Each of these axes has strategic objectives aligned with the institutional development plan, making them highly relevant to the institution's development. This document reflects the most relevant results of Bermúdez & Ortiz (2020), who, aligned with the axis of Smart Living, generate a solution called virtual cafeteria, which allows purchases, reservation of lunches, display of all the products offered and the rating of the service offered by the cafeteria, being its greatest advantage being cross-platform.